(untitled) (LACCEI, 2024)
In this investigation, we sought to solve a problem that concerns a large part of the recycling companies in the world, which consists of the lack of procedures for the control and management of inventories this problem has caused Ecorexcicle S.A.S. an hourly overload in the export process, generating an economic loss due to the payment of overtime and a possible loss of clients due to delays in the delivery of containers. To solve this problem, it was decided to implement a procedure manual for inventory management and control through the 5s quality methodology, which, together with the integration of the components of the COSO II methodology, was optimized by 72 % the loading time of the containers and the release of 124 square meters of the main warehouse.